2021
DOI: 10.1063/5.0069560
|View full text |Cite
|
Sign up to set email alerts
|

Flow examination in abdominal aortic aneurysms: Reduced-order models driven by in vitro data and spectral proper orthogonal decomposition

Abstract: Although flow characteristics in abdominal aortic aneurysms (AAAs) have been extensively studied, they have not found their way into the clinical evaluation of the disease. We, therefore, present experimental AAA flow models, optimized using spectral proper orthogonal decomposition, to aid in gauging AAA severity based on the underlying flow. The resulting reduced-order AAA flow models capture pertinent pathological flow features. With progressive aneurysm expansion, the flow becomes increasingly complex, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The energy-based ranking of modes is performed such that the flow can be accurately reconstructed using a discrete quantity of these modes 2 , thus reducing the order of the system. The flow is said to be accurately represented by the ensemble of modes containing 98% of the total KE which, in cardiovascular flows, has been widely reported to occur within the first 1-10 modes 17,29,8,48 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy-based ranking of modes is performed such that the flow can be accurately reconstructed using a discrete quantity of these modes 2 , thus reducing the order of the system. The flow is said to be accurately represented by the ensemble of modes containing 98% of the total KE which, in cardiovascular flows, has been widely reported to occur within the first 1-10 modes 17,29,8,48 .…”
Section: Methodsmentioning
confidence: 99%
“…Due to the energy-based nature of this analysis, modes may not retain physical inter-pretability due to frequency mixing 2 . Nevertheless, POD analysis offers a means of examining how the fluid KE is distributed amongst coherent flow structures and how this energy changes over time, facilitating a decoupling of spatial and temporal behaviour which can provide valuable insights into the behaviour of the flow 29 . For example, POD analysis of the flow in ruptured and unruptured aneurysms showed that rupture was more strongly associated with spatial flow complexity, rather than temporal stability 8 ; similar insights may be available in the context of aneurysmal TBAD.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy-based ranking of modes is performed such that the flow can be accurately reconstructed using a reduced number of these modes [17], thus reducing the order of the system. The flow is said to be accurately represented by the ensemble of modes containing 98% of the total KE which, in cardiovascular flows, has been widely reported to occur within the first 1-10 modes [16,19,33].…”
Section: Flow Decompositionmentioning
confidence: 99%